Research Directions in Handheld AR - Billinghurst, Mark N.; Henrysson, Anders (International Journal of Virtual Reality, 2006)
Handheld mobile devices are an exciting new platform for Augmented Reality (AR). Mobile phones and PDAs have the potential to provide AR experiences to hundreds of millions of consumers. However, before widespread use can occur there are some obstacles that must be overcome. In particular, developers must consider the hardware and software capabilities of mobile devices and how these can be used to provide an effective AR experience. They must also develop AR interaction metaphors suitable for handheld AR. In this paper we review current and previous research in the field, provide design guidelines and outline future research directions